Examining the Role of Sibling Interaction in Multiethnic-racial Identity Development in the United States. Issue 1 (2nd January 2020) - Cardwell, Megan E.; Soliz, Jordan
ABSTRACT: Ethnic-racial identity (ERI) is tied to wellbeing, especially for ethnic-racial minority individuals, and the process of ERI development is inherently social. However, much of the research on ERI development has focused on ethnic-racial socialization processes between parents and children, despite the fact that sibling relationships tend to be integral to individuals' development and adjustment. Further, ethnic-racial socialization research tends to focus on monoethnic-racial individuals, despite the increasing evidence of the unique benefits and challenges faced by multiethnic-racial (ME-R) individuals. Thus, the purpose of this study is to determine the role that sibling interaction plays in ME-R identity development. Twenty-one ME-R individuals were interviewed about their ME-R identity development process as well as what it was like growing up as a ME-R individual with siblings. Interviews were analyzed using a grounded theory approach and results show that there are three major ways that siblings affect ME-R identity development: through shaping the process of engaging with difference, through sibling conversations, and through the benefits of sibling individuality in shaping ethnic-racial identity. Implications and opportunities for future research are discussed.